Antioxidant effects of ginger, cinnamon and combination on Streptozotocin-induced hyperglycemia associated oxidative stress in rats - ElSadek, Mohamed Farouk; Almajwal, Ali Madi; Abulmeaty, Mahmoud Mustafa Ali (Progress in Nutrition, 2016)
The objective of this study was to examine the various chemical properties of the honey samples acquired from 20 different locations in the Hizan district of the Bitlis province. All samples were acquired from the apiarists who are members of the Hizan Beekepers Association. To this end; analyses have been carried out for moisture, insoluble solid substance, diastasis activity, electrical conductivity, proline, ash, total sugar, free acidity, HMF, fructose ratio, glucose ratio, fructose/glucose ratio in 100 g, fructose+glucose amount in 100 g in terms of grams. The moisture values of the samples were determined to vary between 15.44%- 17.28%, insoluble solid substance amount was determined to vary between 0.001% - 0.080%, diastasis number between 10.0 mg/100 g - 26.1 mg/100 g, electrical conductivity value between 0.18 ms/cm-1 - 0.25 ms/cm-1, proline amount between 414.2 mg/kg - 880.8 mg/kg, ash amount between 0.01% - 0.07%, total sugar average between 69.09% - 75.28%, free acidity value between 16.0 meq/kg - 26.1 meq/kg, HMF value between 6.5 mg/kg - 20.8 mg/kg, fructose ratio between 27.9 mg/100 g - 41.3 mg/100 g, glucose ratio between 30.6 mg/100 g - 34.6 mg/100 g, fructose/glucose ratio between 1.19 g/100 g - 1.28 g/100 g, fructose+glucose amount in 100 grams in terms of grams was determined to vary between 67.5 g/100g - 75.9 g/100 g. It was determined that none of the honey samples contained maltose and that only the samples acquired from Gayda and Keklik villages had very small amounts such as 2.7 mg/100 g and 2.1 mg/100 g. It was determined as a result of the studies carried out on the honey samples that especially proline amount was high. The fact that there was no sucrose in any of the honey samples except two put forth that no sugar has been used for feeding the bees. It was observed that the results were in accordance with the EU standards as well as the Turkish Food Codex Notification on Honey.